ANALISIS PENGARUH SISTEM PENGENDALIAN INTERNAL DALAM PENCEGAHAN KREDIT MACET PADA BUMDES BERSAMA BAGUS KECAMATAN PUJON - Maulidah Faradina; Dwiyani Sudaryanti; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This Study aims to determine and analyze the infuence of the control environment, risk estimation, control activities, informan and communication and monitoring activities on bad loans in BUMDes Bersama Bagus Pujon District. This research was conducted in BUMDes Bersama Bagus Pujon District, using purposive sampling method and the number of respondents was 30 people. The analytical technique used in ther partial test (t). The results of this study suggest that the control environment has a positive and significant effect on bad loans, risk assessment has a positive and insignificant effect on bad loans, control activities have a negative and significant effect on bad loans, information and communication has a negative and significant effect on bad loans, monitoring activities have a significant and negative effect on bad loans. negative and significant to bad loans.Keyword: Internal Control System, Non Performing Loans, BUMDes Bersama